PENOKOHAN, ALUR, LATAR, TEMA, DAN AMANAT DALAM NOVEL BIDADARI-BIDADARI SURGA KARYA TERE LIYE - Lianti, Astepia; Suwardo, FX (Educatio Vitae, 2015)
This study aims to identify and explain the characterizations, plot, setting, theme, and the mandate in novel "Bidadari-bidadari Surga" by Tere Liye. This study   uses   descriptive   qualitative   approach,   the   research   was   based   on descriptive data in the form of sentences and paragraphs that support aspects studied. The depiction of figures was done by using expository and dramatic.The main character is Laisa, while additional figures are Mamak Lainuri, Dalimunte, Ikanuri, Wibisana, Yashinta, Wak Burhan, Cie Hui, and Goughsky. The plot used is backwards plot ( flashback ). Places where the story happened were Lahambay valley, capital of the province, Mount Gede, Rome airport, the Netherlands, and Mount Semeru. The time frame was around 1965 to 2008, morning, noon, night, midnight, and dawn. Social background is among farmers, people who still like to work together, the people who are still envious of the lives of others, and they who have a better family life. The major theme is sacrifice, while the minor theme is love of a sister to her youngsters and her hard work for their education. The mandate given to the reader, were ( 1 ) hard work will make better life, ( 2 ) learn from a mistake, and ( 3 ) finding a mate should not only consider the physical appearance ( beauty ).